Survey Kriteria Standar Usaha 7 Lokasi Wisata di Kabupaten Manggarai Barat Tahun 2019 - Ernesta Leha; Daniel Wolo; Ana S Rahmawati; Yohanes Y W Kean (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2021)
As one of the leading destinations, Labuan Bajo offers several natural tourist attractions that are no less interesting. However, some destinations do not yet have a tourism ecosystem management that can balance ethics, aesthetics, economy, and locality to create excellence in quality tourist destinations. The University of Flores' research team has conducted a survey of standard facilities or standard criteria in 7 tourist sites in the West Manggarai district. The seven locations include Tado Village, Melo Traditional Village, Padar Island, Komodo Island, Rangko Cave, Batu Cermin Cave, Senanggoang Lake. The survey conducted aims to capture tourist destinations from three aspects, namely product, service, and management. Based on the results of the survey that has been conducted, it can be said that: several standard facilities in 7 tourist destinations have not been met. Suggestions are given to the Regency Government and managers of tourist destinations in West Manggarai Regency to work together to procure existing facilities and facilities so that tourism objects in the 7 locations become more organized and advanced.